2022
DOI: 10.1155/2022/3586290
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Nursing Based on the Kano Model in Emergency Multiple Injuries

Abstract: Multiple injury refers to the injury of two or more anatomical parts of the body caused by mechanical injury factors. Even if only one injury exists alone, it can endanger limbs or lives. Therefore, nursing plays an important role in its treatment. Here, we investigated the application and clinical effect of nursing based on the Kano model in emergency multiple injuries. A case-control study was designed, where 48 patients with multiple injuries in the emergency department were divided into the control group t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This suggests that our nursing workers should not only pay attention to the learning of theoretical knowledge and the improvement of nursing skills, but also strengthen the communication with the family members of children to improve the quality of nursing and reduce the occurrence of medical disputes and complaints. In One-dimensional quality, there is a linear relationship between the degree of satisfaction of the child’s family and satisfaction, i.e., when that need is met, the child’s family feels satisfied and vice versa ( Lin et al, 2022 ). The results of this survey show that the demand for “bedside examination of comatose children whenever possible” and “able to pacify children and prevent them from rejecting EEG monitoring equipment” is high.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that our nursing workers should not only pay attention to the learning of theoretical knowledge and the improvement of nursing skills, but also strengthen the communication with the family members of children to improve the quality of nursing and reduce the occurrence of medical disputes and complaints. In One-dimensional quality, there is a linear relationship between the degree of satisfaction of the child’s family and satisfaction, i.e., when that need is met, the child’s family feels satisfied and vice versa ( Lin et al, 2022 ). The results of this survey show that the demand for “bedside examination of comatose children whenever possible” and “able to pacify children and prevent them from rejecting EEG monitoring equipment” is high.…”
Section: Discussionmentioning
confidence: 99%
“…P3(Hospital distance) is negatively correlated with housing price, and the absolute value of the coefficient is the largest. This phenomenon should be due to scarce hospital resources, and if acute diseases occur, shortening the distance to the hospital can greatly improve the survival rate [16]. According to the statistics of Wuhan Municipal Health Commission, in 2019, the elderly population above 65 in Wuhan has accounted for 14.74%, so the demand for medical resources is more vigorous.…”
Section: Position Featurementioning
confidence: 99%
“…Most recent studies employ Kano models to identify quality attributes that address patient needs and improve service quality. These studies have demonstrated a reduction in adverse events, improved prognosis, and increased patient (Barrios-Ipenza et al, 2021; Chen et al, 2019; Lin et al, 2022) . However, the healthcare system comprises numerous subsystems, including hospitals with specialty units, clinics, and daycare centers, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted March 30, 2024. ; https://doi.org/10. 1101/2024.03.30.24305047 doi: medRxiv preprint et al, 2021Chen et al, 2019;Lin et al, 2022) . However, the healthcare system comprises numerous subsystems, including hospitals with specialty units, clinics, and daycare centers, among others.…”
Section: Introductionmentioning
confidence: 99%